Analisis Variasi Bahasa Sosiolek di SMA Negeri 8 Palembang: Kajian Sosiolinguistik - Siti Sumarni; Ayu Puspita Indah Sari (Universitas Muhammadiyah Surabaya, 2026)
Based on the background of the problem, the formulation of the problem of this research is How is the variation of sociolect language in interactions at SMA Negeri 8 Palembang. The purpose of this Research Problem Formulation is to describe the variation of sociolect language in interactions at SMA Negeri 8 Palembang. The research method that will be used is a qualitative research method with a sociolinguistic approach. Based on the research results obtained consisting of 8 data acrolects, 4 data basilects, 1 data vulgar, 6 data slang, 6 data colloquial, 3 data jargon, 1 data Argot, 1 data ken. The results of the research obtained from the use of